An evolutionarily-conserved Wnt3/β-catenin/Sp5 feedback loop restricts head organizer activity in Hydra - Matthias C. Vogg; Leonardo Beccari; Laura Iglesias Ollé; Christine Rampon; Sophie Vriz; Chrystelle Perruchoud; Yvan Wenger; Brigitte Galliot (Nature Communications, 2019)
Hydra regenerate various body parts on amputation by activation of the appropriate organiser, but how head formation is controlled is unclear. Here, the authors identify the transcription factor Sp5 as restricting head formation, by being activated by beta-catenin and then acting as a repressor of Wnt3.